PREPARATION OF ACECLOFENAC PRODRUGS, IN VITRO AND IN VIVO EVALUATION - DURGAPRASAD KEMISETTI,; SARANGAPANI MANDA,; SHOBHA RANI SATLA,; JITHAN AUKUNURU,; NAGA KISHORE RAPAKA, (International Journal of Pharma and Bio Sciences, 2014)
The aim of this study was to synthesize prodrugs of aceclofenac, chemically is a phenyl acetic acid derivative used as NSAID (Non Steroidal Anti Inflammatory Drug) for treatment of osteoarthritis, rheumatoid arthritis and ankylosing spondylitis. The main adverse effect, associated with the drug is upper G.I tract complications and has to be used along with an H2 antagonist to overcome the adverse effect. Hence, prodrugs of aceclofenac were prepared by using PEG 1500 (polyethylene glycol) and PEG 6000 as polymeric backbone and a linker glycine an aminoacid. The prodrugs prepared were characterized by FT-I.R and N.M.R. In vitro dissolution study revealed the drug release from the prodrugs, was higher at pH 7.2 than at pH 1.2. In vivo evaluation studies of the prodrugs, for anti inflammatory activity, and ulcer protection activity, all the prodrugs retained their activity found to be more protective towards ulcers than the standard drug.